Changes in cerebral blood flow in Asperger syndrome during theory of mind tasks presented by the auditory route. - Wendt TN; Metsaihonkala L; Kulomaki T; Aalto S; Autti T; Vanhala R; Von Wendt L (European Child & Adolescent Psychiatry, 2003)
Lack of theory of mind (TOM) has been considered to be a key feature in Asperger syndrome (AS). The main aim of the present study was to determine whether an exclusively auditory input of ToM stories activated the same brain areas as demonstrated previously using visual stimuli. Eight right-handed otherwise healthy men with AS and eight healthy right-handed male controls participated in a PET activation study using auditory given ToM stories and stories about physical events for induction. Both subjects with AS and controls showed increased activation in the occipitotemporal area bilaterally and in thalamus during ToM tasks. Both groups also showed activation in the medial frontal area during ToM tests. However, this activation was more intensive and extensive in the control group, especially when a more sensitive analysis method was used. As a group, unrelated to the tasks, the AS subjects showed increased activation of the cerebellum. It was concluded that the activation pattern was mainly in agreement with earlier studies using comparable stimuli administered differently. There was no support for a right hemisphere specific dysfunction.